2017
DOI: 10.18632/oncotarget.14878
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of exosome-mediated intercellular communication in vascular remodeling

Abstract: Vascular remodeling refers to the alternations of function and structure in vasculature. A complex autocrine/paracrine set of cellular interaction is involved in vascular remodeling. Exosome, a newly identified natural nanocarrier and intercellular messenger, plays a pivotal role in regulating cell-to-cell communication. Exosome emerges as an important mediator in the process of vascular remodeling, showing the most prognostic and therapeutic potent in vascular diseases. Benefiting from exosomal trafficking, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 102 publications
1
66
0
Order By: Relevance
“…It has been reported that MSC engraftment reduces vascular remodelling after coronary vessel balloon injury, this was demonstrated by a lower I/M, neointimal area and positive expression of PCNA in addition to enhanced re‐endothelialisation after MSC transplantation . Several studies have reported that exosomes derived from stem cells could target endothelial cells to promote the pro‐angiogenic effect after myocardial infarction, and exosomes derived from MSC could target VSMC to promote an anti‐inflammatory effect . In a rat model of balloon‐induced vascular injury, exosomes isolated from EPCs accelerated the process of re‐endothelialisation in vivo and enhanced endothelial function in vitro .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been reported that MSC engraftment reduces vascular remodelling after coronary vessel balloon injury, this was demonstrated by a lower I/M, neointimal area and positive expression of PCNA in addition to enhanced re‐endothelialisation after MSC transplantation . Several studies have reported that exosomes derived from stem cells could target endothelial cells to promote the pro‐angiogenic effect after myocardial infarction, and exosomes derived from MSC could target VSMC to promote an anti‐inflammatory effect . In a rat model of balloon‐induced vascular injury, exosomes isolated from EPCs accelerated the process of re‐endothelialisation in vivo and enhanced endothelial function in vitro .…”
Section: Discussionmentioning
confidence: 96%
“…Accumulating evidence suggests that exosome‐derived miRNAs may be involved in the regulation of various aspects of neointima formation via the modulation of target cell functions (eg proliferation and migration of VSMCs) and the resulting effects on vasculature homeostasis . It has been reported that MSC engraftment reduces vascular remodelling after coronary vessel balloon injury, this was demonstrated by a lower I/M, neointimal area and positive expression of PCNA in addition to enhanced re‐endothelialisation after MSC transplantation .…”
Section: Discussionmentioning
confidence: 99%
“…These cell contents, when transferred to recipient cells, can alter its biologic behavior, including intracellular signaling pathways 10 . Exosomal contents, therefore, have the ability to act as either tumor suppressors or promoters through their direct actions on a cell or by modifying the microenvironment 13, 14, 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that exosomes play important roles as carriers of intercellular signals during cancer invasion and vascular remodeling . In the present study, we extracted exosomes from TGF‐β pretreated A549 cell culture supernatant (Texo) and untreated A549 cell culture supernatant (exo).…”
Section: Resultsmentioning
confidence: 99%